The Covid-19 Presence Monitoring System in Water uses Biosensors and Artificial Intelligence based on the Internet of Things - Chintya Tribhuana Utami; Nur Wulan Maudini; Riska Aprilia (Jurnal Rekayasa Sistem & Industri, 2021)
Water is a source of life for humans, therefore its quality needs to be maintained in order to avoidcontamination of COVID-19. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) orCOVID-19 is a pandemic virus that attacks the respiratory system and it is contagious to humans.Therefore, we need a system that can monitor and detect this virus in surface water sources. Earlydetection of water contaminated by COVID-19 is important to solve problems in handling the quality ofwater contaminated with the virus or not. The proposed monitoring system consists of several tools andprocesses including biosensors, microcontrollers, classification using K Nearest Neighbor (K-NN) todetect contaminated water or not, and firebase as data storage. Classification results are stored in firebaseand displayed on the frontend application based on the web. The frontend application can be accessed bythe user. The frontend application also displays a graph that describes the water content periodically and areference for the location of the water area contaminated by the virus is displayed.